Efficacy and safety of open‐label ixekizumab treatment in Japanese patients with moderate‐to‐severe plaque psoriasis, erythrodermic psoriasis and generalized pustular psoriasis. (30th October 2014) - Saeki, H.; Nakagawa, H.; Ishii, T.; Morisaki, Y.; Aoki, T.; Berclaz, P.‐Y.; Heffernan, M.
Abstract Background Ixekizumab, an anti‐IL‐17A monoclonal antibody, demonstrated a high level of efficacy in moderate‐to‐severe plaque psoriasis (PP) patients. Objective To evaluate the efficacy and safety of open‐label ixekizumab in Japanese patients with moderate‐to‐severe PP, erythrodermic psoriasis (EP) and generalized pustular psoriasis (GPP). Methods Patients received 160‐mg subcutaneous ixekizumab injection at Week 0, 80‐mg every 2 weeks through Week 12 and 80‐mg every 4 weeks through Week 24. Efficacy and safety are reported through 24 weeks; additional safety data are available for some patients. Results A total of 78 patients with PP, 8 with EP and 5 with GPP enrolled. In PP patients, PASI75 and PASI90 response rates were 98.7% (77/78) and 83.3% (65/78) at Week 12 respectively. In EP patients, PASI75 and PASI90 were 100.0% (8/8) and 62.5% (5/8) and in GPP patients were 80.0% (4/5) and 60.0% (3/5). Overall, 84.0% (76/91) had a treatment‐emergent AE through ≥24 weeks. There were no serious AEs, deaths, cases of tuberculosis or invasive fungal infections. Limitations No control group and small sample sizes, especially for EP and GPP. Conclusion By Week 12, nearly all patients with PP, EP and GPP achieved PASI75. The safety profile was consistent with reported results and no unexpected safety signals were observed.